A Survey of Training for Temporary Hemodialysis Catheter Insertion During Nephrology Fellowship in Canada: An Update. Issue 1 (September 2019) - Hae, Richard; Samaha, Daniel; Brown, Pierre-Antoine; McQuillan, Rory; Hiremath, Swapnil; Clark, Edward G.
Background: Controversy exists as to whether the insertion of temporary hemodialysis catheters (THDCs) should remain a mandatory requirement of nephrology fellowship training in Canada. A survey conducted by our group in 2012 showed that many nephrology trainees reported inadequate training to achieve procedural competence. Objective: To determine the current practices and training of the insertion of THDCs in nephrology fellowship programs in Canada and how this has evolved since 2012. Design: A survey study was designed comprising the following sections: demographics, details regarding the number and types of THDCs inserted within the past 6 months of fellowship training, adherence to sterile techniques, the use of ultrasound guidance during THDC insertion, training for THDC insertion received before and during nephrology fellowship, and self-perceived adequacy of training and competence in THDC insertion. Setting: The survey was distributed by e-mail in May 2018 either directly or through Canadian nephrology training programs. Participants: Current trainees of Canadian adult nephrology training programs. Measurements: Descriptive statistics were used to analyze the summarized data. The means and interquartile ranges (IQRs) were used to summarize the number of THDC insertions performed, and the categorical data, including data on training and self-perceived competency, were reported using frequencies and percentages. A chi-squared test was used to evaluate the relationship between those who received simulation-based training and self-perceived confidence in either internal jugular or femoral catheter insertion. Methods: An online survey, available in both English and French, was distributed to all adult nephrology trainees in Canada in May 2018 either directly or through their respective programs. Results: Completed surveys were received from 46 of 136 nephrology trainees across Canada (34%). Of those who responded, the median (IQR) number of combined femoral and/or internal jugular THDCs inserted in the past 6 months of fellowship training was 3 (1-6). Eight respondents (17%) indicated that they had not inserted a THDC in the past 6 months. However, only 7 of 42 respondents (17%) indicated that they did not feel competent or adequately trained to perform either femoral or internal jugular THDC insertion. Limitations: Limitations of the study include participation of trainees at different stages of their training. Many trainees indicated that it was not a requirement to keep a formal log of their procedures performed and likely had recall bias when reporting their procedure details. Conclusions: Nephrology fellows in Canada are performing fewer THDC insertions compared to 2012 but report higher levels of self-perceived competence and better training. This may be as a result of significantly more simulation-based training. Our data suggest that training to procedural mastery using simulation-based techniques may be a path to ensuring adequate training for THDC insertion despite fewer procedures being performed during training.